2002
DOI: 10.1006/jcis.2001.8044
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Starch-Based Colloidal Microgels

Abstract: Novel starch microgels were prepared by emulsion cross-linking and characterized with respect to shape, volume, and mass density. Starch microgels appear to be negatively charged (∼−50 mV), with a particle size varying as a function of the type of cross-linker (ca. 0.25-10 µm). Environmental scanning electron microscopy observations show a dependence of the particle swelling on the cross-linking density. Viscosimetry reveals that starch microgels behave as charged polymers, where the reduced viscosity increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The fact that no TSTP peaks can be identified suggests that few or no crosslinker remained in a crystal state inside the microparticles. This result was consistent with that Dziechciarek et al (2002) reported. However, different observation was reported by Malafaya et al (2006).…”
Section: Structural Organization By Xrdsupporting
confidence: 96%
See 2 more Smart Citations
“…The fact that no TSTP peaks can be identified suggests that few or no crosslinker remained in a crystal state inside the microparticles. This result was consistent with that Dziechciarek et al (2002) reported. However, different observation was reported by Malafaya et al (2006).…”
Section: Structural Organization By Xrdsupporting
confidence: 96%
“…Particularly, few studies have concerned about the effect of crosslinking density on the physical properties and loading capacity of TSMs. Moreover, conflicting results on the structural organization of TSMs were reported by different researchers (Dziechciarek et al, 2002;Malafaya et al, 2006). Therefore, these issues will need further study.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chemical crosslinking has been a predominant approach of solidification (Yu and Liu, 1994;Dziechciarek et al, 2002;Li et al, 2009), but non-covalent approaches relying on recrystallization (Reslow et al, 2002) have also been used. This approach has been used to make microcapsules for different purposes within the field of controlled release.…”
Section: Microspheres Produced In Atpsmentioning
confidence: 99%
“…A variety of methods based upon high‐power ultrasonication, microemulsion crosslinking, nanoprecipitation, enzymolysis and recrystallization and so on have been developed to synthesize SNPs. Nanoprecipitation is one of the most effective methods for preparing SNPs; this approach is also called the solvent exchange method, in which starch granules are dissolved in a solvent and precipitated in a nonsolvent to obtain SNPs.…”
Section: Introductionmentioning
confidence: 99%